Produção de forragem de Tifton 85 adubado com nitrogênio e submetido à lotação contínua - Fagundes, Jailson Lara; Moreira, Andréia Luciane; de Paula Freitas, Acyr Wanderley; Zonta, Augusto; Henrichs, Reges [UNESP]; Rocha, Fernanda Cipriano (My University, 2012)
The present assay was conducted at the Research and Development of Adamantina, SP, of the Agência Paulista de Tecnologia dos Agronegócios (APTA) - Pólo da Alta Paulista to evaluate the effect of nitrogen fertilization on morphological composition, density of tillers, leaf area index, light interception and herbage accumulation in grazed Tifton 85 subjected to continuous stocking system. The treatments consisted of four levels of nitrogen (0; 100; 200 and 400kg/ha/year of N), arranged in a randomized complete blocks experimental design with four replications. The grasslands of Cynodon cv. Tifton 85 studied influenced the time of evaluation and of nitrogen levels with a marked effect in morphological composition of the pasture, leaf area index, light interception and population density of tillers that were instrumental in the accumulation of forage. It was found a positive linear effect of nitrogen fertilization on the density of vegetative tillers, totals and herbage accumulation nitrogen fertilization had a marked effect on the amount of total and vegetative tillers, leaf area index in light interception and herbage accumulation. The cultivar Tifton 85 has not reached the necessary conditions for crop growth rate maximum when managed under continuous stocking keeping the grass to 10cm tall.
Forage production of Tifton 85 fertilized with nitrogen and subjected to continuous stocking
Keywords: Cynodon spp.; Grazing; Ovine; Structural characteristics; Ovis